Peptoniphilus duerdenii sp nov and Peptoniphilus koenoeneniae sp nov., isolated from human clinical specimens - ÜLGER, NURVER (SOC GENERAL MICROBIOLOGY, 2012)
Two previously uncharacterized strains of Gram-reaction-positive, anaerobic, coccus-shaped bacteria, designated strains WAL 18896(T) and WAL 18898(T), were recovered from human wound specimens and characterized using phenotypic, chemotaxonomic and molecular taxonomic methods. Comparative 16S rRNA gene sequence analysis and chemotaxonomic and biochemical characteristics demonstrated that these organisms are genotypically and phenotypically distinct and represent previously unidentified sublines within the order Clostridiales in the phylum Firmicutes. Pairwise sequence analysis demonstrated that the novel organisms had 91.9% sequence similarity to each other and were most closely related to members of the genus Peptoniphilus. The major long-chain fatty acids of both strains were C-16:0, C-18:0, C-18:1 omega 9C and C-18:2 omega 6,9c. Based on the phenotypic and phylogenetic findings, strains WAL 18896(T) (=CCUG 56065(T) =ATCC BAA-1640(T)) and WAL 18898(T) (=CCUG 56067(T) =ATCC BAA-1638(T) =DSM 22616(T)) represent two novel species, for which the names Peptoniphilus duerdenil sp. nov. and Peptoniphilus koenoeneniae sp. nov. are proposed, respectively.
Keywords: POSITIVE ANAEROBIC COCCI; GEN. NOV; IDENTIFICATION; ACID; PEPTOSTREPTOCOCCUS; PROPOSAL; MEMBERS